Influence of fixed abrasive configuration on the polishing process of silicon wafers. Issue 1 (January 2017) - Fang, Congfu; Zhao, Zaixing; Lu, Longyuan; Lin, Yanfen
Abstract Lapping and polishing with fixed abrasives is an efficient method to flatten wafers and obtain mirror surface finish. One of the most concerned things is abrasive configuration for polishing pads in research. Researching on pad's abrasive configuration will help get better wafer surface quality. For abrasive trajectories can heavily affect wafer surface flatness and roughness during lapping and polishing process, the present work was conducted to study the relationship among abrasive configuration, trajectory distribution, material removal, and its influence on wafer surface quality. For this purpose, an abrasive configuration method was applied by adopting a written Matlab program to give set values of the radial distance and the initial angle of abrasives fixed on the pad surface. Based on the method, polishing pads with the regular and radial configurations were designed and used to study trajectory distributions under different polishing parameters. The polishing experiments were carried out on silicon wafers with the regular and the radial diamond polishing pads made by the sol-gel method. The wafer surface morphology, thickness, and roughness were detected in polishing. The results show that better flatness and roughness distributions can be obtained through using the radial pad than that of the regular pad, which is due to the smaller value of variation coefficient of the standard deviation for trajectory density and better global profile of trajectory density. The method of pad design and trajectory analysis can be an effective way to design pads with proper abrasive configurations for different applications in lapping and polishing process.